When Objects Go Wandering - Helena Motoh (Asian Studies)
This paper examines the phenomenon of “wandering objects” through the lens of the Skušek Collection, the largest collection of East Asian objects in Slovenia, which was brought to Ljubljana by Ivan Skušek Jr. and his Japanese wife, Tsuneko Kondō Kawase, in 1920. This collection, which traversed private ownership and eventual institutionalisation, illustrates the dynamic mobility of artefacts. This study focuses on the movement of these objects both within and outside the family network, exploring how they were dispersed and sometimes reintegrated into the collection. By analysing specific cases, such as the three Japanese screens and other key objects, this paper identifies unique mobility patterns that differ from more common notions of dissociation and “orphaning” in the research of museum collections. The findings highlight the symbolic roles these “wandering objects” played in reinforcing social ties and cultural identity. This research contributes to a broader understanding of object mobility and provenance, offering a new conceptual framework for the research of private and institutional collections.